Key Findings and Recommendations Based on the USDA Forest Service Integrated Resource Restoration Pilot Third-Party Review. Issue 1 (2nd February 2017) - Schultz, Courtney A; Moseley, Cassandra; Mattor, Katherine M; McIntyre, Kathleen; Ellison, Autumn
Abstract: In 2012 the US Department of Agriculture Forest Service piloted a change in the National Forest System's budget structure and performance measurement system to support integrated restoration. The integrated resource restoration (IRR) budget approach was meant to promote greater integration, prioritization, flexibility, and efficiency for planning and implementation of restoration projects on national forests. We conducted a third-party review of the pilot over three years to understand how the IRR was changing approaches to strategic planning, whether it was having the intended effects, and how aspects of organizational design were affecting success under the IRR. Our review took place in three phases, including interviews with regional- and forest-level staff in 2013, a survey of 1, 210 staff in 2014, and outreach with partners in 2015. We found that the IRR affected strategic planning at the forest and regional levels. Although staff responses overall regarding the effectiveness of the IRR were mixed, some aspects appear to have been more successful than others. Over half of line officers indicated the IRR had resulted in improved integration and prioritization on their forests. If the pilot continues, the agency will need to continue to refine how to determine restoration priorities, measure outcomes, and communicate success.